Comparing the burden of illness of haemophilia between resource‐constrained and unconstrained countries: the São Paulo–Toronto Hemophilia Study. Issue 5 (24th April 2017) - Carneiro, J. D. A.; Blanchette, V.; Ozelo, M. C.; Antunes, S. V.; Villaca, P. R.; Young, N. L.; Castro, D.; Brandão, L. R.; Carcao, M.; Abad, A.; Feldman, B. M.; ,
Abstract : Introduction: Although the regular replacement of clotting factor concentrates (prophylaxis) has been well established as the standard of care for severe haemophilia, the high cost of factor concentrates has limited access to prophylaxis in countries with under‐developed or developing economies. Aims: We studied the health gap that could be addressed by providing unlimited access to clotting factor concentrates with implementation of long‐term prophylaxis initiated from an early age in life. Methods: We performed a cross‐sectional study of a random, representative sample of boys with moderate and severe haemophilia at three haemophilia treatment centres in Sao Paulo, Brazil, and one centre in Toronto, Canada. Results: Canadian subjects were more often treated with prophylaxis, and began treatment at an earlier age. Fewer Canadian subjects had bleeds within the preceding 6 months (19 vs. 34, P = 0.003). Canadian subjects had lower (better) Pettersson radiographic scores (1.5 vs. 6.0, P = 0.0016), lower (better) Hemophilia Joint Health Scores (5.5 vs. 10.5, P = 0.0038), higher (better) Activity Scale for Kids scores (96.6 vs. 92.0, P = 0.033), more time spent in vigorous activity, and higher (better) social participation scores. Conclusions: Our findings suggest that increasing access to clotting factor concentrates for young boys with severe haemophilia is a global imperative.